2018
DOI: 10.3390/su10103409
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Consumers’ Attitudes toward a Theme Park: A Focus on Disneyland in the Los Angeles Metropolitan Area

Abstract: We explore the impact of consumers’ attitude toward a theme park on the image of the host city. We study how attitudinal aspects of Disneyland in Los Angeles can influence the image of Los Angeles. Using the tripartite approach of attitudes, we model consumers’ attitude of theme parks with three dimensions: cognition, affect, and conation. We show the causal relationships among Disney content, attitudinal constructs, and attitudes toward Los Angeles. Results showed that Disney content influenced cognition, aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
1
10
1
Order By: Relevance
“…Theme parks represent a preferred mode of entertainment, generally intended for family visitors [1]. Theme parks comprise one of the most popular entertainment options in the world [2][3][4]. According to the Themed Entertainment Association and AECOM [5], approximately 244 million people worldwide visited the top 25 theme parks by the end of 2017 and 134 million visited the top 20 amusement/theme parks in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theme parks represent a preferred mode of entertainment, generally intended for family visitors [1]. Theme parks comprise one of the most popular entertainment options in the world [2][3][4]. According to the Themed Entertainment Association and AECOM [5], approximately 244 million people worldwide visited the top 25 theme parks by the end of 2017 and 134 million visited the top 20 amusement/theme parks in the Asia-Pacific region.…”
Section: Introductionmentioning
confidence: 99%
“…Brakus et al [11] also suggested investigating the antecedents and consequences of the brand experience. Although Bae et al [2] examined the roles of theme parks in enhancing cities' brand images, few scholars have explored visitors' brand experiences in theme parks, especially in terms of historical and cultural themes. Drawing upon the brand experience concept, this study investigates structural relationships between theme-park-related antecedents (i.e., attributes), visitors' brand experiences, and consequences (i.e., visitors' perceived values, satisfaction, and behavioral intentions).…”
Section: Introductionmentioning
confidence: 99%
“…Users are exposed to image of places, symbols, and representations, with which they elaborate meanings, and with which a particular place can be identified. This is vital both for visitors and for residents [4,29].…”
Section: Brand and Identitymentioning
confidence: 99%
“…Initial literature stream of store brands focus mainly on the existence of store brands validity and profitability of their introduction. The work done by Raju, Sethuraman, and Dhar (1995) is one of the studies that initiated such research stream [12]. They analyze a grocery market including bakery and deli products and frozen goods product categories that consists of three players: two manufacturers selling a national brand and a common retailer who introduces a store brand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They analyze a grocery market including bakery and deli products and frozen goods product categories that consists of three players: two manufacturers selling a national brand and a common retailer who introduces a store brand. Raju et al (1995) solve for equilibrium solutions using a linear demand system and show the tendency of store brands to increase the retailer's category profit when the cross-price sensitivity among national brands is low and the cross-price sensitivity between the national brands and the store brand is high [12]. Some other works also explain what role store brands can play as a leveraging effect [13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%